Taking Situatedness Seriously. Embedding Affective Intentionality in Forms of Living - von Maur, Imke (Frontiers in Psychology, 2021)
Situated approaches to affectivity overcome an outdated individualistic perspective on emotions by emphasizing the role embodiment and environment play in affective dynamics. Yet, their focus lies on the present situation and they adopt a largely functionalist approach by conceiving of emotions and the environment as resources to be regulated or scaffolds to be used. This approach does not go far enough. In this paper I argue that we need to take situatedness seriously: We need to acknowledge that emotions are not situated in undetermined “contexts” but in concrete socio-culturally specific practices referring to forms of living. To do so I offer a multidimensional approach to situatedness that integrates the biographical and cultural dimensions of contextualization within the analysis of situative affective dynamics. This framework allows to see that humans affectively disclose meaning (together) which is at once product and producer of specific forms of living – and these are always already subjects to (politically relevant) critique.